2006
DOI: 10.1103/physrevstab.9.102002
|View full text |Cite
|
Sign up to set email alerts
|

Indirect methods for wake potential integration

Abstract: The development of the modern accelerator and free-electron laser projects requires to consider wake fields of very short bunches in arbitrary three dimensional structures. To obtain the wake numerically by direct integration is difficult, since it takes a long time for the scattered fields to catch up to the bunch. On the other hand no general algorithm for indirect wake field integration is available in the literature so far. In this paper we review the known indirect methods to compute wake potentials in ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 13 publications
0
37
0
Order By: Relevance
“…(1). In this paper, we used the ECHO code [1,2] to carry out an extensive study of the dependence of the wakefield on the transverse geometric parameters. For a tapered collimator, we have shown that the short-range wakefield, for s=d & 0:3 and & =3, is well approximated by Eq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1). In this paper, we used the ECHO code [1,2] to carry out an extensive study of the dependence of the wakefield on the transverse geometric parameters. For a tapered collimator, we have shown that the short-range wakefield, for s=d & 0:3 and & =3, is well approximated by Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Progress in understanding this subject has been achieved through both analytical and numerical studies. In this paper, using the 2D electromagnetic simulation ECHO code [1,2], we carry out an investigation of the longitudinal short-range wakefield due to an axisymmetric collimator. We consider the highly relativistic limit in which a particle traveling at the speed of light c, passes through a step function or tapered collimator illustrated in Figs.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the short-range wake potential of a short bunch in long accelerator structures, direct time domain calculations of wake field are commonly made with the moving window technique and indirect integration methods [8]- [11] are often used in order to dramatically reduce the calculation time in a computer code. In the following, we shall review the implementation of indirect methods for wake potential integration.…”
Section: Wake Potential Calculationmentioning
confidence: 99%
“…For axis-symmetric structures, the infinite integration of wake potential can be replaced by a finite range of integration with the Napoly-Chin-Zotter (NCZ) indirect integration method [11]. Especially, selecting the integration path along the boundary surface of a structure as the path (i) shown in Fig.…”
Section: Wake Potential Calculationmentioning
confidence: 99%
See 1 more Smart Citation